EFFECTS OF NATURAL VENTILATION SYSTEM WITH UNDERGROUND PIPE ON CALF BARN CONDITIONS IN WINTER - Unal SIRIN; Mustafa OKUROGLU (Journal of Animal and Plant Sciences, 2024)
The aim of the present study was to investigate the effects of natural ventilation system with underground pipe which is an alternative ventilation system for temperature, relative humidity and air flow rate parameters in the calf stall indoor environment during the winter, when animals continuously stay in the barn. The temperature, relative humidity and air flow rate values of stall interior and outdoor air were continuously measured during the months of December, January, February, March by applying natural ventilation system with underground pipe and traditional ventilation system with windows in a 48 head calf barn with a floor area of 150 m2. Measured parameters in both ventilation systems were statistically compared.In the wake of implementing; It has been observed that the natural ventilation system with underground pipe in the calf barn in frigid meteorological conditions has a statistically better good achieve on the temperature, relative moisture and air flow rate criteria inside the stall than the traditional ventilation system carried out with windows.In the natural ventilation system with underground pipe, the outside air is taken from the exterior surface of ones of the lengthy sides of the barn, passes under the barn floor transversely and enters the stall from inner surface of the other lengthy side of the barn. Thus, outside air coming in the stall through underground pipes becomes warmer than the outside air picked up into the barn by windows. In addition, since the air taken into the barn with the underground pipe ventilation system penetrates directly into the ground and comes out of the chimneys, it allows the air inside the barn to be cleaned faster than traditional ventilation systems.
Keywords: calf stable; natural ventilation; underground piped natural ventilation; temperature; relative humidity